Eksistensi Jamaah Tarekat Qodiriyah Wa Naqsabadiyah Di Yayasan Pendidikan Islam Al-Hidayah Satron - Hinayatulohi, Ahmad (Mazalat: Jurnal Pemikiran Islam, 2024)
Qodiriyah Wa Naqsabandiyyah is the largest school of tarekat in Islamic Treasures in Indonesia. Tasikmalaya is a home base in East Priangan for the development of this tarekat. The journey of the spread of the tarekat reached various corners in Tasikmalaya to the Satron area. The existence of the tarekat in the satron became the spirit in the development of Islam. This study aims to find out the existence of the Qodiriyah wa Naqsabandiyyah Tarekat at the Al-Hidayah Satron Foundation.  This study uses a descriptive qualitative approach to obtain more in-depth data through observational studies, interviews and documentation. The results of this study show that the Tarekat brought by K.H. Mahfud Murodi in implementing the activities of his Tarekat has several routine activities that are carried out. Among them, 1) Reboan Routine. This activity is a routine study carried out once a week by all Naqsabandiyah Tarekat worshippers. 2) Routine of each DKM (Mosque Prosperity Council). 3) Tajadud (renewal of Baiat). 4) Commemoration of Isra Mi'raj of the Prophet Muhammad SAW.